2008
DOI: 10.1021/jm800649q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyfluoro Ketones for Selective Inhibition of Human Phospholipase A2 Enzymes

Abstract: The development of selective inhibitors for individual PLA 2 enzymes is necessary in order to target PLA 2 -specific signaling pathways; but it is challenging due to the observed promiscuity of known PLA 2 inhibitors. In the current work, we present the development and application of a variety of synthetic routes to produce pentafluoro, tetrafluoro and trifluoro derivatives of activated carbonyl groups in order to screen for selective inhibitors and characterize the chemical properties that can lead to selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 64 publications
0
59
0
3
Order By: Relevance
“…1). Similarly, the hormone-sensitive lipase/FAAH/MAGL inhibitor CAY10499 (30 M) and the intracellular PLA 2 (iPLA 2 ) inhibitor FKGK11 (10 M) (Baskakis et al, 2008;Muccioli et al, 2008;Minkkilä et al, 2009) were incapable of inhibiting the orexin response (Supplemental Fig. 1 The results showed that the radioactivity released upon orexin receptor stimulation was found both in free AA and in the endocannabinoid 2-AG (Fig.…”
Section: Orexin-induced Arachidonic Acid and Endocannabinoid Release 161mentioning
confidence: 96%
“…1). Similarly, the hormone-sensitive lipase/FAAH/MAGL inhibitor CAY10499 (30 M) and the intracellular PLA 2 (iPLA 2 ) inhibitor FKGK11 (10 M) (Baskakis et al, 2008;Muccioli et al, 2008;Minkkilä et al, 2009) were incapable of inhibiting the orexin response (Supplemental Fig. 1 The results showed that the radioactivity released upon orexin receptor stimulation was found both in free AA and in the endocannabinoid 2-AG (Fig.…”
Section: Orexin-induced Arachidonic Acid and Endocannabinoid Release 161mentioning
confidence: 96%
“…To study the effects of iPLA 2 inhibition on NKCC2 phosphorylation and protein abundance, cells were treated with BEL (5 M; Sigma-Aldrich), (R)-BEL, and (S)-BEL (5 M; Cayman Chemical) for 1 h. The concentration for BEL treatment has been previously shown to inhibit rat iPLA 2␤ and -␥ by 100 and 80%, respectively (21). In addition, cells were treated for 1 h with either the novel iPLA2␤ inhibitor FKGK 11 (10 M; Cayman Chemical), with the nonspecific PLA2 inhibitor methyl arachidonyl fluoro-phosphate (MAFP; 100 M; Cayman Chemical), or the inhibitor of phosphatidate phosphohydrolase (PAPH) propranolol (250 M; Sigma Aldrich) (3,5,25). After treatment, cells were either collected for protein biochemistry or processed for immunofluorescence as previously described (31,41).…”
Section: Methodsmentioning
confidence: 99%
“…We thus expanded our initial inhibitor discovery work first to mammalian sPLA 2 s (112), including the use of antisense technology (113), and then to other PLA 2 groups-especially the intracellular cPLA 2 and iPLA 2 -by activated ketones (114,115), fluorophosphonates (116), and other traditional inhibitors (98). In the last decade, this has expanded into a long collaboration with Professor George Kokotos from the University of Athens (9), in which we are designing and testing novel inhibitors including oxoamides (117-120), polyfluoroketones (121,122), and thiazolyl ketones (123). Specifically, we've leaned on insights from molecular dynamics and simulations to inform rational drug design and medicinal chemistry efforts capped off with extensive biochemical characterization.…”
Section: A Turning Point For Lipid Signalingmentioning
confidence: 99%